PENINGKATAN KEMAMPUAN BAHASA ASING UNTUK PERHOTELAN BAGI PELAJAR SMK MUHAMMADIYAH 1 MOYUDAN - Romi Bhakti Hartarto; Khalifany Ash Shidiqi; Tri Anggoro; Beryl Raditya Fawwaz; Nita Viviani Nurhanifah; Syadan Hussein Ismail (Jurnal Berdaya Mandiri, 2025)
SMK Muhammadiyah 1 Moyudan in Sleman Regency, Yogyakarta, is a vocational education institution focusing on the hospitality sector. However, students from grades X to XII face challenges in mastering English, particularly speaking and listening skills, which are crucial in this industry. These limitations can affect their confidence in communicating with foreign guests and hinder their readiness to enter an increasingly globalized workforce. To address this issue, a practice-based training program has been implemented to improve students' English-speaking skills. This program includes awareness sessions on the importance of English in the hospitality industry and interactive simulations with professional scenarios involving native English speakers. Findings from a one-sample paired t-test on 36 participants of the community service program showed an increase of 3.28 points in students' understanding of the importance of English proficiency in the hospitality industry, with a significance level of 1%. This indicates that the community service activity successfully enhanced participants' awareness of the importance of English in the hospitality sector. Keyword: English, Community Empowerment, Vocational Training, Hospitality